Investigating Emotionality: Psychology, Aesthetics, and the Global Mental Health Crisis (KULT_online, 2017)
A Cultural Approach to Emotional Disorders. Psychological and Aesthetic Interpretations by E. Deidre Pribram investigates a wide range of topics, such as the psychological conception of self and the figure of the mad genius or medical diagnostics and neurological research. It thus not only contributes to the analysis of what is commonly referred to as the global mental health crisis or an inquiry into the relationship between the psy disciplines and aesthetic practice, but also – on a broader level – examines the potential of cultural theory in the study of emotions.